Acute mitral valve regurgitation causing severe alveolar hemorrhage. Issue 1 (20th April 2020) - Sakamoto, Ayaka; Enomoto, Yuki; Watabe, Hiroaki; Koyama, Yasuaki; Matsumoto, Yukei; Shimojo, Nobutake; Marushima, Aiki; Kawano, Satoru; Inoue, Yoshiaki
Abstract : Background: Acute mitral regurgitation could occur without common symptoms like hemodynamic instability, but with dyspnea, hemoptysis, and right‐sided infiltration on radiography. We report a case of severe alveolar hemorrhage caused by acute mitral regurgitation, which occurred in the absence of shock. Case Presentation: A 40‐year‐old man presented with dyspnea with bloody phlegm and hypoxia, despite being hemodynamically stable. Chest radiography revealed right‐sided infiltration, and bronchoscopy showed fresh bloody phlegm in his tracheae. No specific findings were detected with any tests. After treatment with several medications and support with extracorporeal membrane oxygenation, his condition improved, although the etiology of the disease remained unknown. Transthoracic and transesophageal echocardiogram revealed severe mitral valve regurgitation with ruptured mitral chordae tendineae. These suggested that the sudden onset of mitral valve regurgitation had caused severe alveolar hemorrhage. Conclusion: Severe alveolar hemorrhage, especially with right‐sided infiltration on chest radiography, should be considered a symptom of acute mitral regurgitation. Abstract : Acute mitral regurgitation could occur without common symptoms like hemodynamic instability, but with dyspnea, hemoptysis, and right‐sided infiltration on radiography. Severe alveolar hemorrhage, especially with right‐sided infiltration on chest radiography, should be considered a symptom of acute mitral regurgitation.